Intra-abdominal Infections: The Role of Anaerobes, Enterococci, Fungi, and Multidrug-Resistant Organisms. (20th December 2016) - Marcus, Gil; Levy, Samuel; Salhab, Ghaleb; Mengesha, Bethlehem; Tzuman, Oran; Shur, Shira; Burke, Erica; Mayeda, Rebecca Cruz; Cochavi, Lior; Perluk, Idan; Zaidenstein, Ronit; Lazarovitch, Tsilia; et al.
Abstract: Background: Intra-abdominal infections (IAI) constitute a common reason for hospitalization. However, there is lack of standardization in empiric management of (1) anaerobes, (2) enterococci, (3) fungi, and (4) multidrug-resistant organisms (MDRO). The recommendation is to institute empiric coverage for some of these organisms in "high-risk community-acquired" or in "healthcare-associated" infections (HCAI), but exact definitions are not provided. Methods: Epidemiological study of IAI was conducted at Assaf Harofeh Medical Center (May–November 2013). Logistic and Cox regressions were used to analyze predictors and outcomes of IAI, respectively. The performances of established HCAI definitions to predict MDRO-IAI upon admission were calculated by receiver operating characteristic (ROC) curve analyses. Results: After reviewing 8219 discharge notes, 253 consecutive patients were enrolled (43 [17%] children). There were 116 patients with appendicitis, 93 biliary infections, and 17 with diverticulitis. Cultures were obtained from 88 patients (35%), and 44 of them (50%) yielded a microbiologically confirmed IAI: 9% fungal, 11% enterococcal, 25% anaerobic, and 34% MDRO. Eighty percent of MDRO-IAIs were present upon admission, but the area under the ROC curve of predicting MDRO-IAI upon admission by the commonly used HCAI definitions were low (0.73 and 0.69). Independent predictors for MDRO-IAI were advanced age and active malignancy. Conclusions: Multidrug-resistant organism-IAIs are common, and empiric broad-spectrum coverage is important among elderly patients with active malignancy, even if the infection onset was outside the hospital setting, regardless of current HCAI definitions. Outcomes analyses suggest that empiric regimens should routinely contain antianaerobes (except for biliary IAI); however, empiric antienterococcal or antifungals regimens are seldom needed.